2005
DOI: 10.1007/s00114-005-0636-y
|View full text |Cite
|
Sign up to set email alerts
|

On the success of a swindle: pollination by deception in orchids

Abstract: A standing enigma in pollination ecology is the evolution of pollinator attraction without offering reward in about one third of all orchid species. Here I review concepts of pollination by deception, and in particular recent findings in the pollination syndromes of food deception and sexual deception in orchids. Deceptive orchids mimic floral signals of rewarding plants (food deception) or mating signals of receptive females (sexual deception) to attract pollen vectors. In some food deceptive orchids, similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
321
0
8

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 316 publications
(329 citation statements)
references
References 103 publications
0
321
0
8
Order By: Relevance
“…The function of these features may be to imitate nectar presence. Variation in fragrance is often observed for deceptive orchids (Schiestl 2005) and odour complexity may be less than for the model species (Raguso 2004, after Wiemer et al 2008.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The function of these features may be to imitate nectar presence. Variation in fragrance is often observed for deceptive orchids (Schiestl 2005) and odour complexity may be less than for the model species (Raguso 2004, after Wiemer et al 2008.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of a spur is usually associated with a nectar reward. However, approximately one third of orchid species are regarded as deceitful (sexual, food, or brood site deception; van der Pijl and Dodson 1969;van der Cingel 1995;Neiland and Wilcock 1998;Cozzolino and Widmer 2005;Schiestl 2005;Tremblay et al 2005;Cozzolino and Scopece 2008;Bell et al 2009;Claessens and Kleynen 2009;Jersáková et al 2009;Vereecken 2009). The presence of a spur, even if nectarless, noticeably increases the possibility of floral pollination in the orchids (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that these color patterns are critically important for plant-pollinator interactions (1)(2)(3)(4)(5)(6)(7)(8). Among the most captivating examples are deceptive orchids that display floral pigment patterns remarkably similar to female bees or wasps to lure male counterparts for pseudocopulation, thereby achieving pollination (9)(10)(11). Despite the obvious aesthetic and ecological significance of these flower color patterns, the molecular mechanisms of pigment pattern formation is not well understood, nor is the genetic basis underlying pattern variation between related species in nature.…”
mentioning
confidence: 99%
“…It is still an enigma in pollination biology that one-third of orchid species are estimated to be deceptive (Dafni 1984, Nilsson 1992, Schiestl 2005, Cozzolino and Widmer 2005. These orchids rely on two main kinds of deception to attract pollinators, including generalized resemblance to food-sources (Nilsson 1983a(Nilsson , 1992Dafni 1984), and specific resemblance to other rewarding flowers (Dafni , 1987Nilsson 1983b;Johnson 1994Johnson , 2000.…”
mentioning
confidence: 99%
“…These orchids rely on two main kinds of deception to attract pollinators, including generalized resemblance to food-sources (Nilsson 1983a(Nilsson , 1992Dafni 1984), and specific resemblance to other rewarding flowers (Dafni , 1987Nilsson 1983b;Johnson 1994Johnson , 2000. The former is assumed to be common among orchids (Dafni 1984), but the latter has been demonstrated rarely (Schiestl 2005).…”
mentioning
confidence: 99%